A Review on the Current Status and Future Trends of Energy-Saving Technologies for Marine Diesel Engines - Fu, Yongkang (Scientific Journal of Technology, 2026)
Driven by tightening decarbonization requirements in international shipping and persistent pressure on total cost of ownership, improving the efficiency of marine diesel engines remains a near- to mid-term cornerstone for fuel and greenhouse-gas reduction. This review summarizes the regulatory drivers and energy-efficiency metrics, discusses the underlying loss mechanisms in marine diesel engines, and provides an expanded overview of major energy-saving technology pathways, including combustion and injection optimization, advanced turbocharging and air handling, Miller-cycle-based cycle improvement, waste-heat recovery and turbocompounding, friction and auxiliary-power reduction, and digital energy-efficiency management. Typical retrofit routes under EEXI/CII compliance, engineering constraints (backpressure, off-design behavior, reliability, maintenance), and techno-economic considerations are highlighted. Finally, the paper outlines development trends toward fuel-flexible engine platforms, low-load efficiency enhancement, modularized WHR solutions, hybridization, and well-to-wake/life-cycle-based assessment frameworks, offering references for both academic research and practical engineering implementation.